Effects of the Y-shape stud and outer insulating layer on heat dissipation and wall temperature of the hot cyclone in a circulating fluidized bed boiler. (5th March 2022) - Yao, Yuge; Huang, Zhong; Zhang, Man; Yang, Hairui; Lyu, Junfu; Wang, Jialin
Highlights: The heat dissipation process of a hot cyclone was numerically simulated. Three key parameters of the heat dissipation were well linear with stud number. The arrangement had a slight impact on heat dissipation at a certain stud number. The insulating layer may let the steel layer temperature increase rapidly. Suggestions for the hot cyclone wall design were given. Abstract: The hot cyclones in circulating fluidized bed (CFB) boilers often face the problems of high heat dissipation and high wall temperature in the operation, which may decrease the strength of the steel layer and present a danger to workers. To solve these problems, the heat dissipation characteristics through the cyclone wall and the key parameters of this process need to be known. In this study, a numerical simulation was conducted to estimate the wall temperature field of a hot cyclone in a 440 t/h CFB boiler. The effects of the Y-shape stud arrangement and the outer insulating layer on the heat flux and the wall temperature were qualitatively and also quantitatively analyzed. It was found that the Y-shape stud does enhance the heat dissipation of the cyclone wall. A denser Y-shape stud arrangement results in higher temperatures of the steel layer and also the outer surface. Moreover, the heat flux of the inner surface, the maximum temperature of the steel layer, and the outer surface are all well linear with the stud number. However, how the studs arrange on the steel layer has very sight effects on the heat flux and wall temperature at a certain stud number. Adding an insulating layer on the outer wall surface can reduce the heat dissipating capacity of the hot cyclone and also decrease the outer surface temperature. The effects of Y-shape studs on the heat dissipation and wall temperature are also weakened. While the outer insulating layer results in a rapid increase of the steel layer temperature, which may bring extra risk to the cyclone wall. Based on the simulation results, reducing the unnecessary studs and covering an insulating layer thinner than 20 mm are suggested.